2018
DOI: 10.1007/s00439-018-1867-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the demographic history of the Himalayan and adjoining populations

Abstract: The rugged topography of the Himalayan region has hindered large-scale human migrations, population admixture and assimilation. Such complexity in geographical structure might have facilitated the existence of several small isolated communities in this region. We have genotyped about 850,000 autosomal markers among 35 individuals belonging to the four major populations inhabiting the Himalaya and adjoining regions. In addition, we have genotyped 794 individuals belonging to 16 ethnic groups from the same regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
(47 reference statements)
1
26
0
Order By: Relevance
“…The most southern population sampled during that study was represented by a single haplotype, which indicated either a recent genetic bottleneck or a founding event followed by little to no additional immigration. Comparisons between mitochondrial DNA (mtDNA) and nuclear DNA (nucDNA) shed light on maternal and paternal lineages and potential population structuring by sex-biased dispersal (Ross & Shoemaker, 1997;Jorde, Bamshad & Rogers, 1998;Goudet, Perrin & Waser, 2002;Ulrich et al, 2009;Ambrose et al, 2014;Tamang et al, 2018). Here we develop and use a suite of microsatellite markers for C. australensis to gain insights into the species' population genetics and evolutionary history through analysis of the phylogeographical structure of three focal populations.…”
Section: Introductionmentioning
confidence: 99%
“…The most southern population sampled during that study was represented by a single haplotype, which indicated either a recent genetic bottleneck or a founding event followed by little to no additional immigration. Comparisons between mitochondrial DNA (mtDNA) and nuclear DNA (nucDNA) shed light on maternal and paternal lineages and potential population structuring by sex-biased dispersal (Ross & Shoemaker, 1997;Jorde, Bamshad & Rogers, 1998;Goudet, Perrin & Waser, 2002;Ulrich et al, 2009;Ambrose et al, 2014;Tamang et al, 2018). Here we develop and use a suite of microsatellite markers for C. australensis to gain insights into the species' population genetics and evolutionary history through analysis of the phylogeographical structure of three focal populations.…”
Section: Introductionmentioning
confidence: 99%
“…We further investigated one outlier sample of Kol which showed high level of East/Southeast Asian ancestry. In the PC analysis, this Kol individual (Kol outlier) aligned along the Trans-Himalayan cline 5 (Fig. 1B).…”
Section: Resultsmentioning
confidence: 93%
“…2). The majority of these minor components were either sporadic or present among some specific language groups 5,8,25 e.g. the Southeast/East Asian components among Mundari and Tibeto-Burman speakers 5,25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an expert on Human Evolutionary Genetics, it is necessary to reiterate that, in India, modern humans have been living for at least 50,000 to 70,000 years and have experienced various kinds of pathogen pressures ( 22 25 ). A large number of genetic and archaeological studies are consistent with a largely local emergence of South Asian ancestry with minor [and in some cases relatively higher e.g., Tibeto-Burmans ( 26 ), Austroasiatics ( 27 ), and some Northwest Indian populations ( 28 )], ancestry contributions from East and West Eurasians respectively ( 29 31 ). Therefore, these long term geographic and genetic isolations, might have certainly helped us to modify our genetic landscape against various kinds of pathogens ( 22 , 25 , 32 34 ).…”
mentioning
confidence: 89%